The THE INFLUENCE OF THE NUMBER OF MSMEs AND FINANCIAL CAPITAL ON THE PERFORMANCE OF Sulaman Indah MSMEs (Case Study of an Embroidery Craft Business in Naras 1 Village, Pariaman City): (Studi Kasus pada Usaha Kerajinan Sulaman di Desa Naras 1 , Kota Pariaman) - Syukrial; Aguslina, Rahayu (Universitas Sumatera Barat, 2023)
This study aims to determine the effect of the number of MSMEs and financial capital on the performance of the embroidery business in Naras 1 Village, Pariaman City. The data sources used are primary and secondary data. Data analysis technique used is descriptive statistical analysis, classical assumption test using normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression analysis and hypothesis testing using partial test (t test), simultaneous test (f test) and Adjusted R Square. The data processing method uses SPSS Version 27 and Microsoft Excel 2021. From the multiple linear results Y = 7.852 + 0.304(X1) + 1.087(X2). The results of the analysis show partially (T test) that the number of SMEs has a significant effect on the performance of the embroidery business by 0.002